2020
DOI: 10.1037/bne0000370
|View full text |Cite
|
Sign up to set email alerts
|

A role for neurogenesis in probabilistic reward learning.

Abstract: Rewards are often unreliable and optimal choice requires behavioral flexibility and learning about the probabilistic nature of uncertain rewards. Probabilistic learning occurs over multiple trials, often without conscious knowledge, and is traditionally associated with striatal function. While the hippocampus is classically recognized for its role in memory for individual experiences, recent work indicates that it is also involved in probabilistic forms of learning but little is known about the features that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 100 publications
(151 reference statements)
0
15
0
Order By: Relevance
“…Preferential targeting by the LEC [37,38], and the extended development of LEC-new neuron plasticity reported here, suggests that adult-born neurons may especially facilitate learning about the cues that make each experience unique. Such a function could contribute to learning about, or responding to, discrete objects and cues [79][80][81][82] (but see [83]). Roles for LEC in learning about cue configurations may also underlie new neuron functions in discrimination between similar contexts and places [39,54,84,85].…”
Section: Implications For Cognition and Agingmentioning
confidence: 99%
“…Preferential targeting by the LEC [37,38], and the extended development of LEC-new neuron plasticity reported here, suggests that adult-born neurons may especially facilitate learning about the cues that make each experience unique. Such a function could contribute to learning about, or responding to, discrete objects and cues [79][80][81][82] (but see [83]). Roles for LEC in learning about cue configurations may also underlie new neuron functions in discrimination between similar contexts and places [39,54,84,85].…”
Section: Implications For Cognition and Agingmentioning
confidence: 99%
“…Adding to this evidence, other human work examining field potentials in the hippocampus shows maximal neural firing in this region when rewards are uncertain (compared to certain), suggesting the hippocampus may be important for computing a reward uncertainty signal (Vanni‐Mercier, Mauguière, Isnard, & Dreher, 2009). Animal studies also implicate the hippocampus in probabilistic value learning, providing additional converging evidence (e.g., Lee, Ghim, Kim, Lee, & Jung, 2012; Seib, Espinueva, Floresco, & Snyder, 2020).…”
Section: Introductionmentioning
confidence: 89%
“…However, we deliberately avoided the use of conjunctive stimuli, opting instead for simple patterns as cues. A recent study by Seib et al (2020) similarly showed impaired reward‐based probabilistic learning using very simple cues in transgenic mice lacking adult hippocampal neurogenesis. Akin to our study, the demands on pattern separation in that study are not obvious.…”
Section: Introductionmentioning
confidence: 96%
“…Key evidence supporting a role for AHN in pattern separation comes from studies in which ablation of neurogenesis resulted in specific impairments in discriminating stimuli with a high degree of spatial similarity or overlap, but not stimuli that are more readily distinguished [10][11][12] . Evidence also supports an important role for AHN in cognitive flexibility and the underlying processes of behavioural inhibition that allows flexible responding in the face of changing contingencies 5 , and elements of cognitive flexibility and behavioural inhibition have been shown to be sensitive to experimental manipulations of AHN [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 89%